Intranasal Delivery of Bone Marrow-Derived Mesenchymal Stem Cells, Macrophages, and Microglia to the Brain in Mouse Models of Alzheimer's and Parkinson's Disease. Issue 1 (January 2014) - Danielyan, Lusine; Beer-Hammer, Sandra; Stolzing, Alexandra; Schäfer, Richard; Siegel, Georg; Fabian, Claire; Kahle, Philipp; Biedermann, Tilo; Lourhmati, Ali; Buadze, Marine; Novakovic, Ana; Proksch, Barbara; et al.
In view of the rapid preclinical development of cell-based therapies for neurodegenerative disorders, traumatic brain injury, and tumors, the safe and efficient delivery and targeting of therapeutic cells to the central nervous system is critical for maintaining therapeutic efficacy and safety in the respective disease models. Our previous data demonstrated therapeutically efficacious and targeted delivery of mesenchymal stem cells (MSCs) to the brain in the rat 6-hydroxydopamine model of Parkinson's disease (PD). The present study examined delivery of bone marrow-derived MSCs, macrophages, and microglia to the brain in a transgenic model of PD [(Thy1)-h[A30P] aS] and an APP/PS1 model of Alzheimer's disease (AD) via intranasal application (INA). INA of microglia in naive BL/6 mice led to targeted and effective delivery of cells to the brain. Quantitative PCR analysis of eGFP DNA showed that the brain contained the highest amount of eGFP-microglia (up to 2.1 × 10 4 ) after INA of 1 × 10 6 cells, while the total amount of cells detected in peripheral organs did not exceed 3.4 × 10 3 . Seven days after INA, MSCs expressing eGFP were detected in the olfactory bulb (OB), cortex, amygdala, striatum, hippocampus, cerebellum, and brainstem of (Thy1)-h[A30P] aS transgenic mice, showing predominant distribution within the OB and brainstem. INA of eGFP-expressing macrophages in 13-month-old APP/PS1 mice led to delivery of cells to the OB, hippocampus, cortex, and cerebellum. Both MSCs and macrophages contained Iba-1-positive population of small microglia-like cells and Iba-1-negative large rounded cells showing either intracellular amyloid β (macrophages in APP/PS1 model) or α-synuclein [MSCs in (Thy1)-h[A30P] aS model] immunoreactivity. Here, we show, for the first time, intranasal delivery of cells to the brain of transgenic PD and AD mouse models. Additional work is needed to determine the optimal dosage (single treatment regimen or repeated administrations) to achieve functional improvement in these mouse models with intranasal microglia/macrophages and MSCs. This manuscript is published as part of the International Association of Neurorestoratology (IANR) special issue of Cell Transplantation .